CONTACT ANALYSIS OF ELASTIC COMPOSITE CYLINDRICAL ROLLER BEARING - YU JiangHong; YANG Wen; LI Chao; YAO QiShui (Jixie qiangdu)
In order to research into the contact between the rolling element and the rollaway nest of the elastic composite cylindrical roller bearing,the finite element method and the classical Hertz contact theory are separately used to calculate the contact stress and being out of shape of the cylindrical roller bearing. The two results have the error of ten percent. Thus the finite element method is verified to be accurate in roller bearing. Since the contact pairs of the inner and outer confine of the two types of roller bearings are similar,the finite element method could be used in the research of the contact stress of the elastic composite cylindrical roller bearing. Calculation and analysis are made on the contact stress,contact half width,contact displacement and the distribution along the axial direction under different burdening. The results show that under a certain burdening,elastic composite cylindrical roller contact displacement and contact half width increase with the expansion of filling degree; Under different burdening,elastic composite cylindrical roller contact stress and equivalent stress both have the minimum value along with the expansion of filling degree,and with the increase of burdening,the change of the minimum value is organized. In terms of contact stress,the elastic composite cylindrical roller bearing is superior to the solid cylindrical roller bearing. Reasonable filling degree can reduce the contact stress of elastic composite cylindrical roller bearings and improve the"edge effect".